2001
DOI: 10.1034/j.1600-0854.2001.20806.x
|View full text |Cite
|
Sign up to set email alerts
|

Clathrin Interactions with C‐Terminal Regions of the Yeast AP‐1 β and γ Subunits are Important for AP‐1 Association with Clathrin Coats

Abstract: Heterotetrameric adaptor (AP) complexes are thought to coordinate cargo recruitment and clathrin assembly during clathrin-coated vesicle biogenesis. We have identified, and characterized the physiological significance of clathrin-binding activities in the two large subunits of the AP-1 complex in Saccharomyces cerevisiae. Using GST-fusion chromatography, two clathrin-binding sites were defined in the beta1 subunit that match consensus clathrin-binding sequences in other mammalian and yeast clathrin-binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 67 publications
(100 reference statements)
2
34
0
3
Order By: Relevance
“…There are many different TGN/endosomal adaptor proteins in yeast (AP-1, Gga1, and Gga2 and the epsin-related proteins Ent3 and Ent5), and disruption of these adaptor genes results in TGN/endosomal sorting phenotypes (Costaguta et al, 2001;Mullins and Bonifacino, 2001;Duncan et al, 2003;Friant et al, 2003;Eugster et al, 2004). However, in studies in which adaptor proteins containing CBM mutations were analyzed, no significant phenotypes were observed (Mullins and Bonifacino, 2001;Yeung and Payne, 2001). At least four endocytic adaptors have been studied in yeast-the epsin-related proteins Ent1 and Ent2 and the AP180 homologues Yap1801 and Yap1802-and all four possess C-terminal CBMs in which the carboxylic acid at the end of the polypeptide substitutes for the final polar residue in the motif.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…There are many different TGN/endosomal adaptor proteins in yeast (AP-1, Gga1, and Gga2 and the epsin-related proteins Ent3 and Ent5), and disruption of these adaptor genes results in TGN/endosomal sorting phenotypes (Costaguta et al, 2001;Mullins and Bonifacino, 2001;Duncan et al, 2003;Friant et al, 2003;Eugster et al, 2004). However, in studies in which adaptor proteins containing CBM mutations were analyzed, no significant phenotypes were observed (Mullins and Bonifacino, 2001;Yeung and Payne, 2001). At least four endocytic adaptors have been studied in yeast-the epsin-related proteins Ent1 and Ent2 and the AP180 homologues Yap1801 and Yap1802-and all four possess C-terminal CBMs in which the carboxylic acid at the end of the polypeptide substitutes for the final polar residue in the motif.…”
Section: Introductionmentioning
confidence: 94%
“…Likewise, if the TDs containing chc1-box mutations only possess a lower affinity binding site for adaptor-associated CBMs, this low-affinity interaction between AP-1 and clathrin was easily disrupted during the cell fractionation procedure. In previous studies, AP-1 incorporation into CCVs was almost abolished in cells containing mutations to the two CBM sequences in the ␤-subunit (Apl2) and a C-terminal deletion of the clathrin-binding region in the ␥-subunit (Apl4) (Yeung and Payne, 2001). Thus, the reduced AP-1 association with CCVs isolated from chc1-box cells is consistent with these observations and suggests that stable incorporation of AP-1 into CCVs is mediated by the interaction of CBM-containing AP-1 subunits with the TD.…”
Section: Chc1-box Allele Mutations and Clathrin Functionmentioning
confidence: 99%
“…In S. cerevisiae, there are three AP complexes, AP-1, AP-2R, and AP-3 (Yeung et al, 1999), and two GGAs, Gga1p and Gga2p (Costaguta et al, 2001;Dell'Angelica et al, 2000;Hirst et al, 2000). Both AP-1 and Gga1p/Gga2p physically interact with clathrin (Costaguta et al, 2001;Yeung and Payne, 2001;Yeung et al, 1999). It has been suggested that Gga1p and Gga2p are involved in the formation of CCVs in the TGN-to-late endosome transport pathway (Costaguta et al, 2001;Black and Pelham, 2000;Dell'Angelica et al, 2000;Hirst et al, 2000), although the interaction with Arf1p is not sufficient for the Golgi-localization and function of Gga1p/Gga2p (Boman et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The C-terminal region contains two sequences related to the clathrin-binding motif [L (L, I) (D, E, N) (L, F) (D, E)] identified in mammalian clathrin-interacting proteins. 2,15) One sequence, LLDFD (638-642), precisely matches the mammalian consensus sequence, and the other, LLDLF, at the extreme Cterminus (722-726), is very similar to the motif except for one residue. In a previous study, Yeung and Payne reported that the C-terminal region of Apl2p (471-726) interacted with clathrin as detected by immunoblotting analysis.…”
Section: Discussionmentioning
confidence: 99%
“…14) The APL2 gene product, Apl2p, has been predicted to be a 726-amino acid protein and was shown to contain a clathrin-binding motif, LLDFD, at the C-terminal region (located at residues 722-726), 15,16) but the correlation between Apl2p and inositol biosynthesis has not been elucidated.…”
Section: )mentioning
confidence: 99%